AI-Powered Branding by Utilizing ChatGPT for the Promotion of Competitive MSMEs (SDGs9) - Hardini, Inkreswari Retno; Rehatta, Stanny Dewanty; Purba, Regina Humaningtyas; Novianti, Ariska (Universitas Syiah Kuala, 2025)
Karangsong Village in Indramayu Regency holds substantial economic potential in the fisheries, tourism, and creative industry sectors. However, more than 70% of Micro, Small, and Medium Enterprises (MSMEs) in the village still rely on conventional marketing methods. Only around 30% utilize social media, and less than 10% have adopted digital branding strategies effectively. The main challenges faced by these MSMEs lie in the areas of production, business management, and marketing particularly in terms of product quality standardization, financial recordkeeping, inventory management, and the implementation of effective digital promotion strategies. This community engagement program aims to enhance the competitiveness of MSMEs through the application of Artificial Intelligence (AI), particularly by utilizing the ChatGPT platform as a tool to improve the efficiency and quality of digital branding. The program is conducted in four stages: socialization to introduce the concept of AI and ChatGPT, technical training and mentoring, monitoring and evaluation of AI implementation outcomes, and the preparation of a final report along with sustainability recommendations. The solutions offered include using ChatGPT to recommend product innovations, develop business plans, generate promotional content, write social media copy, and create customer engagement chatbots. University students are actively involved in the implementation of the program, in alignment with the Merdeka Belajar Kampus Merdeka (MBKM) initiative. Additionally, the program supports the achievement of Sustainable Development Goal (SDG) 9, which focuses on Industry, Innovation, and Infrastructure. The expected outcomes include AI-based marketing strategies that are practical and implementable for MSMEs, as well as enhanced customer engagement through digital media. This initiative is expected to strengthen the digital capacity of Karangsong's MSMEs in facing the challenges of the digital economy.